Controllability of morphing wing of UAV using shape memory alloy - Sharanya Ramachandran. (2009)
The aim of this project is to study the controllability of a morphing UAV wing flap, actuated by shape memory alloy wires. The morphing wing flap prototype was fabricated by Thomas. In this project, the prototype response with SM495 0.185 mm dia NiTi wire. The wing flap is actuated using SMA, which is trained to possess Two way memory effect. The material is electrically heated during training and flap actuation. Deflection angles,rates are observed. This is performed for 3 conditions; Natural cooling, forced convective cooling, and wing flap with external load. The greatest deflection for a given input power is seen for natural convection, where the flap is able to deflect about 22° with a power of 15 W in 2 wires. Forced convection shows a significant drop (72%) in deflection rate for 8.2 W input power. The trend seen is that, higher the temperature of SMA wire, higher the rate and deflection of angle. The property of constrained recovery and Clausius Clapeyron relationship for dσr/dT is used to explain the observation. Upto slightly above Austenite finish temperature(Af), i.e about 90°C, the recovery stress increases with increase in temperature, accompanied by recovery strain. The change in length due to recovery strain causes the wing flap to deflect. The wing response in the case of external load is dependent on the amount of force that is generated by the actuators to overcome the external load. The above experiments serve as qualitative guidelines to test SMA material actuators for compatibility and performance with a wing flap. It takes into account the various factors that need to be considered during actuation, like the ambient conditions and external load on wing flap, the power consumption in each case. In further research, the author suggests that an empirical formula which shows the relationship between wing response and SMA material properties.